Evaluation of the use of UV radiation and ozone in the degradation of methylparaben - Álvarez-Gómez, Yesmmy (2023)
[Introduction]: Contaminants of emerging concern (CECs) are now a subject of interest for various areas of scientific research, mostly international studies are identified, however, there is still insufficient information on the true effects of these compounds on the environment and on the health of populations that are in contact with these types of contaminants, requiring in turn the search and execution of effective treatments to minimize their bioaccumulation in the environment, especially those substances of pharmaceutical origin, which are already being recognized for their high degree of toxicity. [Objective]: In the present investigation, the degradation of the emerging contaminant methylparaben was studied. [Methodology]: For this study, the distilled water was contaminated, after which the analysis of the effectiveness of ozone, ultraviolet radiation, and the combined treatment of UV radiation and ozonation in the degradation of the substance of pharmaceutical origin was carried out. [Results]: In the study it was found that the combined treatment of UV radiation and ozonation was more effective in the degradation of methylparaben, compared to the techniques of UV and Ozone radiation used separately. [Conclusions]: The results obtained in this research generate information regarding a new alternative that allows the degradation of pharmaceutical contaminants, such as methylparaben, to minimize the environmental impact of this type of substance.